2022
DOI: 10.3390/tropicalmed7090231
|View full text |Cite
|
Sign up to set email alerts
|

Predicting HIV Status among Men Who Have Sex with Men in Bulawayo & Harare, Zimbabwe Using Bio-Behavioural Data, Recurrent Neural Networks, and Machine Learning Techniques

Abstract: HIV and AIDS continue to be major public health concerns globally. Despite significant progress in addressing their impact on the general population and achieving epidemic control, there is a need to improve HIV testing, particularly among men who have sex with men (MSM). This study applied deep and machine learning algorithms such as recurrent neural networks (RNNs), the bagging classifier, gradient boosting classifier, support vector machines, and Naïve Bayes classifier to predict HIV status among MSM using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The SVM is a binary classification technique that classifies data and separates it into two groups by generating an operational separating hyperplane. The support vectors are the data points nearest to the hyperplane, and the hyperplane is a decision space separated into a set of objects of different classes [17,18].…”
Section: Machine Learning Classifiersmentioning
confidence: 99%
“…The SVM is a binary classification technique that classifies data and separates it into two groups by generating an operational separating hyperplane. The support vectors are the data points nearest to the hyperplane, and the hyperplane is a decision space separated into a set of objects of different classes [17,18].…”
Section: Machine Learning Classifiersmentioning
confidence: 99%
“…Three primary studies have been published that used machine learning methods to predict HIV status in Zimbabwe [ 2 , 19 , 20 ]. First, Mutai et al [ 2 ] predicted HIV status using Demographic Health Survey data from Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained from the study by Mutai et al [ 2 ] were not specific to Zimbabwe but sub-Saharan Africa. Second, using data from the Zimbabwe Ministry of Health and Child Care, Chingombe et al [ 19 ] predicted HIV status among men who had sex with men in Zimbabwe’s two major cities, Bulawayo and Harare. The findings of this study were limited to men who had sex with men in Bulawayo and Harare and could not be generalised to other cities in Zimbabwe or the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of HIV infection, key populations include men who have sex with men (MSM), transgender women, sex workers, intravenous drug users and people in prisons and other closed settings. Key populations remain the most crucial driver of the HIV pandemic, with the majority of incident cases occurring in this population [ [1] , [2] , [3] ]. Research has shown that men who have sex with men (MSM) living in sub-Saharan African countries where same-sex sexual conduct is criminalized have a five times higher risk of HIV infection than countries where it is not [ 4 ].…”
mentioning
confidence: 99%